Kesiapan UMKM Tenun Ikat dalam Pemanfaatan Inovasi Teknologi E-Commerce di Kota Kupang - Natalia M R Mamulak (Jurnal Inovasi Kebijakan, 2020)
Weaving Ikat UMKM in Kupang City amounted to 82 groups spread across 6 Districts. Sampling technique for all ikat weaving businesses by segmenting business actors who have, and do not yet have a shop or physical building in a sale and purchase transaction. technological innovation marks a change in economic performance to be technology-based which has higher added value. E-commerce is the process of buying, selling, or exchanging goods, services and information through a computer network, including the Internet. In an effort to develop ikat weaving in order to develop globally, it is necessary to apply digital technology or e-commerce to attract a broad market. In this study using descriptive quantitative, where in quantitative research with this descriptive format aims to explain, summarize various conditions, various situations, or various variables that arise in the community and the object of research is based on what happened. In general, this study uses inductive statistics to analyze research data. Judging from the knowledge of the online sales system, UMKM woven ikat basically knows information about online sales but due to limited knowledge and abilities, MSMEs have not been able to use it. In this regard, weaving SMEs said they were ready to learn and implement an online sales system. In the online purchasing process, the community does not experience obstacles. Based on the results of data analysis of 82 ikat weaving, that: 100% MSME Medium category, 85% MSME Small category and 80% MSME Small category are ready to implement digital e-commerce technology for business development in order to survive and compete globally.